Pengelolaan Dana Peturunan dan Bakatan di Pura Dalem Purwa Banyuning - Luh Ayu Dewi Handayani; Ni Wayan Yulianita Dewi (Universitas Pendidikan Ganesha, 2022)
Pura Dalem Purwa Banyuning is one of the temples in Banyuning that implements a peturunan and bakatan system in obtaining funds. The purpose of this study is to reveal the practice of managing funds peturunan and bakatan at Pura Dalem Purwa Banyuning for temple krama carried out by prajuru. The theory that underlies this research is the theory of stewardship, the concept of tri hita karana, the concept of good governance, and public sector financial management. This research uses descriptive qualitative method. The data were obtained through observation, interview, and documentation techniques. Data processing using Miles and Huberman analysis techniques. The results of this study indicate that the process of managing inheritance and talent funds is carried out in a structured manner starting from the budget planning stage, budget preparation, budget implementation, supervision, and accountability by involving krama's participation in its management, as well as reporting accountability is carried out transparently but not accompanied by physical evidence and only delivered orally